2013
DOI: 10.1111/aeq.12026
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating Capital: Latino Newcomer Young Men in a U.S. Urban High School

Abstract: Newcomer young men confront numerous obstacles that limit their chances for attainment and achievement. Using social and cultural capital frameworks and a case study methodology, this article examines how four Latino newcomer young men navigated an urban U.S. high school. It reveals how teachers and a counselor cultivated capital and how the young men leveraged this capital, thus challenging traditional depictions of Latino immigrant adolescents and highlighting the importance of belonging for these youth. [re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 28 publications
(31 reference statements)
0
30
0
2
Order By: Relevance
“…Through this study, we found that institutional spaces for newcomer youth to reflect on their past and present realities and dislocations provided an opportunity for new analyses and understandings. While many studies on newcomer youth have emphasized the important roles of schools in fostering a sense of belonging (Hopkins et al ; Suárez‐Orozco et al ), our study also found that, in addition, students benefitted from concepts and tools that could offer them the opportunity to analyze and reflect on migration experiences, social inequalities, and rights abuses both back in their home country and in the United States. Many of the youth in the human rights club were very young at the time of their first migrations and underwent dangerous journeys to escape political repression.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Through this study, we found that institutional spaces for newcomer youth to reflect on their past and present realities and dislocations provided an opportunity for new analyses and understandings. While many studies on newcomer youth have emphasized the important roles of schools in fostering a sense of belonging (Hopkins et al ; Suárez‐Orozco et al ), our study also found that, in addition, students benefitted from concepts and tools that could offer them the opportunity to analyze and reflect on migration experiences, social inequalities, and rights abuses both back in their home country and in the United States. Many of the youth in the human rights club were very young at the time of their first migrations and underwent dangerous journeys to escape political repression.…”
Section: Discussionmentioning
confidence: 50%
“…In the field of anthropology of education, while increasing attention is being paid to transnational civic identities (DeJaeghere and McCleary ; Dyrness ), newcomer youth (Bartlett and García ; Fine et al ; Hopkins et al ), and the in‐ and out‐of‐school processes that shape notions of identity and belonging (Abu El‐Haj ; Levinson ; McGinnis ), few ethnographic, school‐based studies of HRE exist and HRE has been undertheorized in terms of how young people make sense and meaning of their experiences, in this case, immigrant and refugee youth. The inquiry approaches of anthropology of education offer important analytical frames and methods to apply to the study of HRE especially because so little research on youth experiences, responses, and meaning making within such programs exists.…”
Section: Human Rights Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Suárez‐Orozco and Suárez‐Orozco (2002) argue that safe, engaging, and relevant schools can help immigrant students feel like they belong in a new country and develop positive multicultural self‐identities. Immigrant students’ academic, economic, and social success in the United States largely depends on how they are received in the host country (Erikson ; Grinberg and Grinberg ; Hopkins et al ). Grinberg and Grinberg's () seminal research on the psychological impacts of migration and exile emphasizes that a sense of belonging is a “requisite for becoming integrated into a new country” (p. 23).…”
Section: Immigrants In Us Schoolsmentioning
confidence: 99%
“…The literature suggests that specialized programs, or separate schools for high school‐ age immigrant students, can be protective if they insulate students from harmful socialization practices associated with acculturation and help students feel as if they belong both at school and in the new country (Bang ; Hacohen ; Heineke et al ). Hopkins et al () reports that newcomers who feel that they belong at their schools have higher self‐efficacy and lower rates of depression. A student's sense of belonging likely increases when schools value students’ home culture and language (Bang ).…”
Section: Immigrants In Us Schoolsmentioning
confidence: 99%